Skewed norms under peer pressure: Formation and collapse - Moti Michaeli; Daniel Spiro (University of Oslo, Department of Economics, 2014)
This paper shows that peer pressure may lead to dynamic convergence to a norm that is skewed with respect to preferences in society, yet is endogenously upheld by the population. Moreover, a skewed norm will often be more sustainable than a representative norm. This may explain the skewness of various social and religious norms. By furthermore interpreting a norm as a political regime, we show that biased regimes can be sustained even without the existence of a powerful group with coherent interests. We analyze the pattern by which political regimes collapse and relate it to contemporary revolutions and mass protests.
Keywords: D02; D03; D72; D74; Z10; Z12; 330; Peer pressure; Social norm; Revolution; Protest movement; Alienation; Religion